Dimensions of Organizational Silence and Intention to Leave. A Quantitative Study among Generation Y Employees in the Private Sector in Jakarta, Indonesia - Lourencia; Singh Kartar Singh, Jugindar; Binti Ahmad, Noraini; Kaur Sarjit Singh, Devinder (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to examine the influence of the dimensions of organizational silence towards intention to leave by Generation Y employees in the private sector in Jakarta. The three dimensions of organizational silence encompass acquiescent silence, defensive silence and prosocial silence. This was a quantitative study that used a survey method to collect primary data from 158 participants. The target population was generation Y employees engaged in the private sector in Jakarta, Indonesia. The data analysis was done by using SPSS tool version 20. The findings revealed that acquiescent silence and defensive had a positive and significant relationship with intention to leave organizations by Generation Y employees. This study provided additional knowledge of the effects of organizational silence on intention to leave. Based on the findings, human resource managers should examine further the consequences of organizational silence and develop policies and procedures to improve the retention of Generation Y employees in the private sector in Jakarta. Leaders in organizations and human resource managers should implement policies to create a workplace where employees will offer ideas and suggestions and express their views openly and safely. This study is the first to examine the relationship between the dimensions of organizational silence and intention to leave by generation Y employees in Jakarta, Indonesia.